ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENDANAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAIVARIABEL MODERATING PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - FARIDA SAGALA (JURNAL ILMIAH MAKSITEK, 2018)
The objective of the research was to examine and analyzesome factors which influenced financing decision in property and real estate companies listed in BEI (Indonesia Stock Exchange) with institutional ownership as moderating variable. The research used comparative casual method. The population was all companies which financial statements had been audited and listed in BEI, and 47 0f them were used as the samples, taken by using census and time series sampling technique so that there were 141 observation samples all together. The data were gathered by conducting documentary study and analyzed by using multiple linear regression analysis and residual test for moderating variable. The result of the research showed that, simultaneously, the variables of firm size, asset structure, and profitability had significant influence on financing decision. Partially, the variables of firm size and profitability which were measured by net profit margin ratio had the influence on financing decision. The result of residual test showed that institutional ownership could moderate the correlation of financing decision withfirm size, asset structure, and profitability.